Treating posttraumatic stress in post-conflict countries and countries that accepted refugees. Report on the STOP-study, a multi-site study on treatment seeking and treatment outcome in people suffering from posttraumatic stress following war and migration in former Yugoslavia. - Schützwohl, Matthias; Bravo-Mehmedbašić, Alma; Frančišković, Tanja; Lečić-Toševski, Dušica; Ljubotina, Damir; McCrone, Paul; Gavrilović, Jelena; Priebe, Stephan; Kučukalić, Abdulah (2004)
War and migration in the Balkans caused traumatic experiences in great parts of it's population. About four million people living in former Yugoslavia as well as about 100, 000 refugees living in different European countries are estimated to suffer from on-going and severe psychological symptoms of post-traumatic stress. Although in need of treatment, many of these people do not seek treatment. Given the fact that, if untreated, post-traumatic stress reactions tend to persist for many years, often resulting in impairment and disability secondary to the symptom complex, offering appropriate care is a special challenge to health services. With regard to this context, an EC-funded multi-centre study including partners from Belgrade (SCO). Dresden (D), London (UK), Rijcka (HR), Sarajevo (BIH), and Zagreb (HR) aims (a) to provide an empirical basis for designing care programmes for people suffering from post-traumatic stress following war and migration in the Balkans who currently do not seek treatment, and (b) to improve the cost-effectiveness of treatment programmes for those patients who are cared for in specialised treatment centres. The paper presents the aims and the design of the STOP study. The first results of the study will be available in 2005.
Projekt MZOS
ENG